圆柱凸轮建模方法分析与研究 - 刘杰; 李强 (Jixie chuandong)
Under the SolidWorkes environment,by the scanning excision and coating features,the feasibility,the modeling method and the modeling procedure of the 3D cylindrical cam are discussed.A simple modeling method is provided for the cylindrical cam,especially for the cylindrical cam with the complex motion,the high acceleration and the high rotating speed,and this provides a basis for the future works like CAE/CAM.